2022
DOI: 10.1088/1748-605x/ac9943
|View full text |Cite
|
Sign up to set email alerts
|

In vitro application of drug-loaded hydrogel combined with 3D-printed porous scaffolds

Abstract: The two main causes of implant surgery failure are aseptic loosening and bacterial-induced implant-associated infections. To make bone defect implants effective for a long time, the ideal scaffold should take into account the two functions of osseointegration and anti-infection. Therefore, on the basis of the low-elastic-modulus Ti-10Ta-2Nb-2Zr (TTNZ) alloys developed by the research group in the early stage, this study intends to combine the vancomycin-loaded hydrogel with the 3D-printed through-hole porous t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 63 publications
(81 reference statements)
0
7
0
2
Order By: Relevance
“…As buscas por referências nas bases de dados não foram restringidas quanto ao tipo de estudo ou quanto ao ano em que foram publicadas, uma vez que o tema abordado pode ser considerado como recente e com escassos estudos em humanos. Dos estudos selecionados, de acordo com os critérios de elegibilidade previamente estabelecidos, somente um possuía um desenho longitudinal com pacientes (Zagra et al 2019); dois eram relatos de casos clínicos (Grillo et al 2020;Pedrosa et al 2021); nove foram feitos in vitro (Casadidio et al 2018;Censi et al 2019;Drago et al 2014;Guan et al 2016;Guzzo et al 2020;Harris et al 2005;Huang et al 2022;Liao et al 2020;Pitarresi et al 2013) e o restante in vivo, utilizando amostras de animais, ratos ou coelhos (ter Boo et al 2016;Ter Boo et al 2018;Boot et al 2020;Boot et al 2017;Giavaresi et al 2014;Gribova et al 2020;Li et al 2020). Nas buscas não foram encontradas revisões sistemáticas, tampouco meta análises.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…As buscas por referências nas bases de dados não foram restringidas quanto ao tipo de estudo ou quanto ao ano em que foram publicadas, uma vez que o tema abordado pode ser considerado como recente e com escassos estudos em humanos. Dos estudos selecionados, de acordo com os critérios de elegibilidade previamente estabelecidos, somente um possuía um desenho longitudinal com pacientes (Zagra et al 2019); dois eram relatos de casos clínicos (Grillo et al 2020;Pedrosa et al 2021); nove foram feitos in vitro (Casadidio et al 2018;Censi et al 2019;Drago et al 2014;Guan et al 2016;Guzzo et al 2020;Harris et al 2005;Huang et al 2022;Liao et al 2020;Pitarresi et al 2013) e o restante in vivo, utilizando amostras de animais, ratos ou coelhos (ter Boo et al 2016;Ter Boo et al 2018;Boot et al 2020;Boot et al 2017;Giavaresi et al 2014;Gribova et al 2020;Li et al 2020). Nas buscas não foram encontradas revisões sistemáticas, tampouco meta análises.…”
Section: Discussionunclassified
“…Quanto aos antimicrobianos associados ao hidrogel, não foram encontradas padronizações relativas ao tipo ou a concentração. A maioria dos estudos testaram somente a vancomicina associada ao hidrogel de AH (Boot et al 2020;Censi et al 2019;Drago et al 2014;Giavaresi et al 2014;Grillo et al 2020;Huang et al 2022;Li et al 2020;Liao et al 2020;Pedrosa et al 2021;Pektas et al 2007;Zagra et al 2019). Ainda que os testes tenham sido feitos somente com a vancomicina, a concentração aplicada nos estudos variou de 2%, 2,5%, 5% ou não foi relatada nas respectivas metodologias.…”
Section: Discussionunclassified
“…There is, therefore, a high risk of bacterial adhesion and colonization on orthopedic implants, leading eventually to biofilm infections [ 24 , 25 , 26 ]. Similar to other medical devices and implants, most orthopedic implants generally fail due to the development of IAIs and poor tissue interconnections [ 27 , 28 ]. Such poor host integration between the implants and their surrounding bone tissues may lead to the presence of small void spaces around implants, allowing a suitable environment for bacterial adhesion and colonization [ 5 , 7 , 12 , 26 ].…”
Section: Biofilm Formation On Orthopedic Implants and Prevention Stra...mentioning
confidence: 99%
“…In recent years, hydrophilic interpenetrating 3D polymeric networks, known also as hydrogels, were reported as suitable materials that can be used in the development of antibacterial coatings [ 76 ]. Owing to the adjustability of the intercommunicating networks of hydrogels, they are attractive for loading antibacterial agents with various molecular weights and physiochemical properties and sustaining their release around the implantation site [ 25 , 28 ]. Among the biopolymers used in the formation of hydrogels, biologically relevant materials, including collagen, gelatin, hyaluronic acid, chitosan, and alginate, are widely used owing to biodegradability, safety, and their capabilities of inducing cell adhesion, growth, and differentiation [ 28 , 81 , 82 ].…”
Section: Biofilm Formation On Orthopedic Implants and Prevention Stra...mentioning
confidence: 99%
“…Hyaluronic acid can be combined with CD44. By inhibiting the expression of interleukin 1β, causing matrix metal prop (MATRIX Metalloproteire-1, MMP-1), MMP-2, MMP-3, MMP-9, and MMP-13 Synthesis decreases, reduce the activity of alien enzymes in arthritis, and promote the proliferation of cartilage cells while lowering the apoptosis of cartilage cells and protecting cartilage ( Huang et al, 2022a ). Studies have shown that the bracket with hyaluronic acid as the material has apparent bone induction effects during the cartilage repair process, which can significantly promote the repair of defects.…”
Section: Polymer Materials For 3d Bio Printing Of Bone and Cartilagementioning
confidence: 99%